Hyperammonemic coma after craniotomy: Hepatic encephalopathy from upper gastrointestinal hemorrhage or valproate side effect?. Issue 15 (April 2017) - Guo, Xiaopeng; Wei, Junji; Gao, Lu; Xing, Bing; Xu, Zhiqin
Abstract: Rationale: Postoperative coma is not uncommon in patients after craniotomy. It generally presents as mental state changes and is usually caused by intracranial hematoma, brain edema, or swelling. Hyperammonemia can also result in postoperative coma; however, it is rarely recognized as a potential cause in coma patients. Hyperammonemic coma is determined through a complicated differential diagnosis, and although it can also be induced as a side effect of valproate (VPA), this cause is frequently unrecognized or confused with upper gastrointestinal hemorrhage (UGH)-induced hepatic encephalopathy. We herein present a case of valproate-induced hyperammonemic encephalopathy (VHE) to illustrate the rarity of such cases and emphasize the importance of correct diagnosis and proper treatment. Patient concerns and diagnoses: A 61-year-old woman with meningioma was admitted into our hospital. Radical resection of the tumor was performed, and the patient recovered well as expected. After administration of valproate for 7 days, the patient was suddenly found in a deep coma, and her mental state deteriorated rapidly. The diagnoses of hepatic encephalopathy was confirmed. However, whether it origins from upper gastrointestinal hemorrhage or valproate side effect is uncertain. Interventions and outcomes: The patient's condition fluctuated without improvement during the subsequent 3 days under the treatment of reducing ammonia. With the discontinuation of valproate treatment, the patient regained complete consciousness within 48 hours, and her blood ammonia decreased to the normal range within 4 days. Lessons subsections: VHE is a rare but serious complication in patients after craniotomy and is diagnosed by mental state changes and elevated blood ammonia. Thus, the regular perioperative administration of VPA, which is frequently neglected as a cause of VHE, should be emphasized. In addition, excluding UGH prior to providing a diagnosis and immediately discontinuing VPA administration are recommended.